(untitled) (Transactions of the Association of European Schools of Planning, 2022)
About 70 percent of Italian municipalities that have fewer than 5,000 inhabitants are located in difficult to access mountain areas which are often prone to multiple hazards. As clearly demonstrated by the seismic events that hit Central Italy in 2016, the socio-economic decline of these municipalities is also increasing their vulnerability. Nowadays, small villages represent an important challenge for Italy, because they require significant resources and effective strategies to both break the cycle of decline and promote their economic and social development, while also reducing their vulnerability to natural and climate related hazards. This contribution provides an overview of the initiatives recently launched in Italy in favour of small villages and outlines a methodological path to assess and enhance the overall resilience of these areas, with a focus on a case study area located in the Basilicata Region of Southern Italy.